1996
DOI: 10.1897/1551-5028(1996)015<1793:pschia>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Synthetic Chlorinated Hydrocarbons in Albatross Tissue Samples From Midway Atoll

Abstract: Abstract-Anthropogenic organic contaminants have been found in even the most remote locations. To assess the global distribution and possible effects of such contaminants, we examined the tissues of two species of albatross collected from Midway Atoll in the central North Pacific Ocean. These birds have an extensive feeding range covering much of the subtropical and northern Pacific Ocean. Anthropogenic contaminants were found at relatively great concentrations in these birds. The sum of 19 polychlorinated bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 29 publications
6
36
0
Order By: Relevance
“…The extreme differences observed between Black-footed and Laysan Albatross contaminant concentrations is not likely due to differences in contaminant metabolism or excretion rates given that both species are closely related genetically (Nunn et al 1996), highly sympatric and known to interbreed (Fisher 1972), and have similar blood protein composition (Brown and Fisher 1966). Previous studies have found comparable PCB congener profile patterns (Jones et al 1996, Guruge et al 2001a as well as PCB metabolite formation (hydroxylated and methylsulfonyl polychlorinated biphenyls) (Klasson-Wehler et al 1998) in Black-footed and Laysan Albatrosses, suggesting these two species metabolize organochlorine compounds in the same way. Organic contaminant concentrations are also heavily influenced by the amount of lipid in the tissue evaluated (Clark et al 1987).…”
Section: Contaminant Differences Between Speciesmentioning
confidence: 83%
See 1 more Smart Citation
“…The extreme differences observed between Black-footed and Laysan Albatross contaminant concentrations is not likely due to differences in contaminant metabolism or excretion rates given that both species are closely related genetically (Nunn et al 1996), highly sympatric and known to interbreed (Fisher 1972), and have similar blood protein composition (Brown and Fisher 1966). Previous studies have found comparable PCB congener profile patterns (Jones et al 1996, Guruge et al 2001a as well as PCB metabolite formation (hydroxylated and methylsulfonyl polychlorinated biphenyls) (Klasson-Wehler et al 1998) in Black-footed and Laysan Albatrosses, suggesting these two species metabolize organochlorine compounds in the same way. Organic contaminant concentrations are also heavily influenced by the amount of lipid in the tissue evaluated (Clark et al 1987).…”
Section: Contaminant Differences Between Speciesmentioning
confidence: 83%
“…Similarities in behavioral and breeding ecology between Black-footed and Laysan Albatrosses (Whittow 1993a, b, Tickell 2000 make these reported differences in contaminant body burden surprising. Previous studies have suggested differences in diet are responsible for Black-footed Albatrosses having greater contaminant body burden concentrations than Laysan Albatrosses (Jones et al 1996, Auman et al 1997, Klasson-Wehler et al 1998). However, these papers did not investigate foraging patterns or diet composition.…”
Section: Introductionmentioning
confidence: 98%
“…The diet of the Laysan albatross consists primarily of ommastrephid squids (ϳ68% of the diet) whereas the black-footed albatross feed mostly on flying fish (50%) and squids constitute a relatively lesser proportion (32%) of the diet. Details regarding the sources of environmental contaminants for these two species of albatrosses have been reported previously [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Relatively high concentrations of chlorinated aromatic compounds, including PCBs and their hydroxylated and methyl sulfone metabolites [24], polychlorinated dibenzo-p-dioxins, and dibenzofurans (PCDD/Fs) and non-ortho-substituted PCBs were found in fat samples from the north Pacific populations [25], while lower concentrations were measured in the south Pacific species [23]. Ortho-substituted PCBs and DDT-related compounds were also reported in plasma samples from the north Pacific populations [26].…”
Section: Introductionmentioning
confidence: 99%